Analisis Strategi Komunikasi Pemasaran dalam Peningkatan Pariwisata Melalui Media Sosial di Kabupaten Langkat - Dina Ika Sintia; Rani Pahira Saputri; Alhafidzh Alhafidzh; Maulana Andinata Dalimunthe; Hasan Sazali (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
In developing a tourist attraction, it is necessary to have publication and marketing support at the local, national and international level, because the success of development and efforts to improve the quality of tourism depends on the effectiveness of marketing activities and a tourist information center is needed. depending on the seriousness of the Regional Government in marketing tourist objects and public awareness, Seeing the decline in the number of tourists in the last 1 (one) year, it is a matter of marketing communication strategies that are less than optimal, especially on publications on social media so that the goals and objectives cannot be achieved by the Tourism and Culture office Langkat Regency. In an effort to increase the number of tourist visits, especially natural tourism, Bukit Lawang and Tangkahan. There needs to be more improvement in the implementation of effective communication that will support the implementation of the tourism marketing communication strategy of the Department of Tourism and Culture. This study uses descriptive research with a qualitative research approach with data collection techniques, observation. By using this method, it was found that the Department of Tourism and Culture Kab. Langkat has its own marketing communication strategy in increasing tourism in Langkat Regency.